Development Of Islamic Religious Education Learning Modules Based On Local Wisdom - Noneng Nurhayani; Indah Sulistiani; Syarifuddin; Rezkiyah Hoesny; Siti Tiara Maulia (IJGIE (International Journal of Graduate of Islamic Education), 2024)
Islamic Religious Education (PAI) has great potential to increase understanding and application of religious values that are in line with local wisdom. However, existing learning modules often do not integrate these two aspects explicitly, resulting in a gap between theory and practice. This research aims to develop a PAI learning module based on local wisdom and assess its effectiveness in increasing student understanding and engagement.This research uses literature research methods, by collecting and analyzing sources relevant to the development of PAI modules and local wisdom. The research results show that learning that integrates PAI with local wisdom not only enriches students' religious knowledge but also increases their understanding of the application of these values in their social and cultural context. The module developed successfully integrates examples of local wisdom that are relevant to PAI subject matter. Initial assessments show positive responses from students as well as increased interest and participation in the learning process.